Constantinian Toleration. (August 2018) - Lloyd, Vincent
Recent secular theorists of toleration have turned to Christian thought as a resource to overcome problems faced by secular-liberal accounts of toleration. This review essay examines three such projects, one in the tradition of Thomistic virtue ethics, another in the tradition of Frankfurt School critical theory, and another in political theory. While Christian ethics can learn from the methods and theoretical machinery deployed in these studies, each study assumes that the question of toleration is posed from a position of power and privilege. The essay asks what it might mean to consider toleration from the perspective of a marginalized community—like the early Christians.